2016
DOI: 10.1016/j.jtcvs.2016.06.040
|View full text |Cite
|
Sign up to set email alerts
|

The value of preoperative 3-dimensional over 2-dimensional valve analysis in predicting recurrent ischemic mitral regurgitation after mitral annuloplasty

Abstract: Objectives Repair for ischemic mitral regurgitation with undersized annuloplasty is characterized by high recurrence rates. We sought to determine the value of pre-repair 3-dimensional echocardiography over 2-dimensional echocardiography in predicting recurrence at 6 months. Methods Intraoperative transesophageal 2-dimensional echocardiography and 3-dimensional echocardiography were performed in 50 patients undergoing undersized annuloplasty for ischemic mitral regurgitation. Two-dimensional echocardiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 33 publications
(30 reference statements)
2
25
0
Order By: Relevance
“…On a day-to-day basis, cardiac surgeons are faced with 2 important questions regarding IMR: Should we operate on this (moderately) regurgitant mitral valve and, Should we repair or replace this (severely) regurgitant mitral valve? As shown by Sun and colleagues 2 and by our group, 6,7 3DE P3TA may be the key to answering these questions. At this point, both questions are difficult to answer for an individual patient based on current guidelines.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…On a day-to-day basis, cardiac surgeons are faced with 2 important questions regarding IMR: Should we operate on this (moderately) regurgitant mitral valve and, Should we repair or replace this (severely) regurgitant mitral valve? As shown by Sun and colleagues 2 and by our group, 6,7 3DE P3TA may be the key to answering these questions. At this point, both questions are difficult to answer for an individual patient based on current guidelines.…”
mentioning
confidence: 81%
“…5 Additional studies from our group with similar modeling algorithms have shown that preoperative 3DE P3TA is a strong (ie, independent) predictor of IMR recurrence after undersized ring annuloplasty for severe IMR 6 and that 3DE is superior over 2-dimensional echocardiography because it is not dependent on viewing plane selection. 7 Those studies and the study by Sun and colleagues 2 are, however, limited by the fact that IMR severity was measured semiquantitatively with jet area/left atrium area. Future IMR studies should include quantitative IMR severity assessment with effective regurgitant orifice area and regurgitant volume.…”
mentioning
confidence: 98%
“…Using three-dimensional echocardiography (3DE) and advanced valve modeling algorithms, we showed that P3 preoperative segmental leaflet tethering is a strong predictor of recurrent IMR 6 months after undersized annuloplasty [5]. In a subsequent study we showed a much higher predictive value of 3DE over two-dimensional echocardiography (2DE) for recurrent IMR [6]. In addition to preoperative 3DE predictors we are also in need of intraoperative (immediate post-repair) 3DE predictors that can guide patientspecific intraoperative surgical decision-making.…”
Section: Introductionmentioning
confidence: 89%
“…Degree of leaflets tethering, quantitated by the precise evaluation of the altered MV morphology in patients with secondary MR, has been associated with failure of MV repair (i.e., MV annuloplasty with significant recurrent MR). Specific echocardiographic indices derived from 2D TTE and TEE as well as 3D TEE modeling, have been identified in several retrospective studies performed in the last decade ( Figure 3, Table 2): the posterior and/or anterior leaflet angles, the mitral annulus dimensions and spatial conformation, the posterior displacement of the mitral leaflet coaptation, the tenting area and/or volume, the tethering length and height (43,(104)(105)(106)(107)(108)(109)(110)(111). The most commonly used cut-offs to determine high degree of MV tethering, and thus high risk of MV repair failure, are the following: posterior leaflet angle >45º, anterior leaflet angle >25º, tenting area ≥2.5 cm 2 , and the tenting height ≥11 mm (Figure 3, Table 2) (9,112).…”
Section: Determining the Likelihood Of A Successful MV Interventionmentioning
confidence: 99%